Fluorescent kinase inhibitors as probes in cancer. (22nd July 2021) - Usama, Syed Muhammad; Zhao, Bosheng; Burgess, Kevin
Abstract : Fluorescent dyes attached to kinase inhibitors (KIs) can be used to probe kinases in vitro, in cells, and in vivo . Abstract : Fluorescent dyes attached to kinase inhibitors (KIs) can be used to probe kinases in vitro, in cells, and in vivo . Ideal characteristics of the dyes vary with their intended applications. Fluorophores used in vitro may inform on kinase active site environments, hence the dyes used should be small and have minimal impact on modes of binding. These probes may have short wavelength emissions since blue fluorophores are perfectly adequate in this context. Thus, for instance, KI fragments that mimic nucleobases may be modified to be fluorescent with minimal perturbation to the kinase inhibitor structure. However, progressively larger dyes, that emit at longer wavelengths, are required for cellular and in vivo work. In cells, it is necessary to have emissions above autofluorescence of biomolecules, and near infrared dyes are needed to enable excitation and observation through tissue in vivo . This review is organized to describe probes intended for applications in vitro, in cells, then in vivo . The readers will observe that the probes featured tend to become larger and responsive to the near infared end of the spectrum as the review progresses. Readers may also be surprised to realize that relatively few dyes have been used for fluorophore-kinase inhibitor conjugates, and the area is open for innovations in the types of fluorophores used.